"I Got My Diagnosis on a Yellow Post-it Note": Young Adult Cancer Patients' Experiences of the Process of Being Diagnosed With Cancer. Issue 4 (July 2019) - Hauken, May Aasebø; Hølge-Hazelton, Bibbi; Larsen, Torill M.B.
Abstract : Background: Cancer in young adults is rare but young adult cancer patients (YACPs) are at an increased risk of severe physical and psychosocial impairments during cancer treatment and survivorship. However, little is known about the onset of this process. Objective: The aim of this study was to explore how young cancer survivors experience the process of being diagnosed with cancer. Methods: A qualitative method founded on a phenomenological-hermeneutical approach was used and included in-depth interviews with 20 young adult survivors (aged 24–35 years) with different cancer diagnoses, analyzed by Systematic Text Condensation. Results: The participants' experiences of the diagnosis process were elaborated according to 3 main themes: (1) "I felt something was wrong, but…, " (2) "The traumatic uncertainty, " and (3) "The day my world collapsed." Conclusion: The findings indicate that the YACPs experienced a diagnosis of cancer as a highly traumatic and long-lasting process, characterized by lack of information and uncertainty. The findings indicate that healthcare professionals do not acknowledge the vulnerable phase of life and transitional challenges of YACPs. Implications for Clinical Practice: The findings highlight the need to raise awareness of cancer in young adulthood in the public and in the primary healthcare system, to shorten the diagnosis process, and to clarify responsibility for age-related information and psychosocial follow-up during the diagnosis process. Further research is highly warranted.